Novel, Soluble Isoform of the Herpes Simplex Virus (HSV) Receptor Nectin1 (or PRR1-HIgR-HveC) Modulates Positively and Negatively Susceptibility to HSV Infection - Lopez, Marc (American Society for Microbiology, 2001)
A novel member of the nectin family, nectin1γ, was molecularly cloned. The cDNA has the same ectodomain as nectin1α and nectin1β, the two known transmembrane isoforms that serve as receptors for herpes simplex virus (HSV) entry into human cell lines (nectin1α and nectin1β, also called PRR1-HveC and HIgR, respectively). The 1.4-kb transcript, which originated by alternative splicing, is expressed in human cell lines, and appears to have a narrow distribution in human tissues. The sequence does not have a hydrophobic anchoring region, and the protein is secreted in the culture medium of cells transfected with the cDNA. Nectin1γ, purified from culture medium, can compete with membrane-bound nectin1β and reduce HSV infectivity. The expression of nectin1γ cDNA in cells resistant to HSV infection and lacking HSV receptors enables HSV to enter the cell, which implies that it is present at the cell surface. Thus, nectin1γ has the potential both to mediate and to reduce HSV entry into cells.